KESUKSESAN IMPLEMETASI SISTEM INFORMASI AKUNTANSI SYARIAH PADA BAITUL MAAL WA TAMWIL (BMT) DI KABUPATEN KLATEN - Sohidin Sohidin; Nurhasan Hamidi; Muhammad Sabandi (Department of Economics Education, Universitas Sebelas Maret, 2017)
This activity aims to trace the use of accounting information systems. The training was held at Sharia Financial Services Cooperative (KJKS) Baitul Maal wa Tamwil (BMT) Ta'awun and BMT Barepan. Both BMTs are located in Klaten District of Central Java Province. The accounting information system was developed based on the regulations set forth in the Principles of Sharia Accounting Standards (PSAK No. 59) and Accounting Guidelines for Indonesian Sharia Banking (PAPSI) issued by Bank Indonesia. The evaluation to determine the impact of the implementation of the information system on performance was done after the training is conducted. Instruments to determine the success of information system implementation developed based on the research from DeLone & McLean (2004), by observing the quality of the system used and the information generated. Evaluation results show that based on the perceptions of BMT employees, the information system that had been trained to them, had impact on performance.